An Edible Biopolymeric Microcapsular Wrapping Integrating Lytic Bacteriophage Particles for Salmonella enterica: Potential for Integration into Poultry Feed - Arthur O. Pereira; Nicole M. A. Barros; Bruna R. Guerrero; Stephen C. Emencheta; Denicezar Â. Baldo; José M. Oliveira Jr; Marta M. D. C. Vila; Victor M. Balcão (MDPI AG, 2023)
This research work aimed at developing an edible biopolymeric microcapsular wrapping (EBMW) integrating lytic bacteriophage particles for Salmonella enterica, with potential application in poultry feed for biocontrol of that pathogen. This pathogen is known as one of the main microorganisms responsible for contamination in the food industry and in foodstuff. The current techniques for decontamination and pathogen control in the food industry can be very expensive, not very selective, and even outdated, such as the use of broad-spectrum antibiotics that end up selecting resistant bacteria. Hence, there is a need for new technologies for pathogen biocontrol. In this context, bacteriophage-based biocontrol appears as a potential alternative. As a cocktail, both phages were able to significantly reduce the bacterial load after 12 h of treatment, at either multiplicity of infection (MOI) 1 and 10, by 84.3% and 87.6%, respectively. Entrapment of the phage virions within the EBMW matrix did not exert any deleterious effect upon their lytic activity. The results obtained showed high promise for integration in poultry feed aiming at controlling Salmonella enterica, since the edible biopolymeric microcapsular wrapping integrating lytic bacteriophage particles developed was successful in maintaining lytic phage viability while fully stabilizing the phage particles.